2017
DOI: 10.1002/hed.24832
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized phase III study comparing a mixture of natural agents versus placebo in the prevention of acute mucositis during chemoradiotherapy for head and neck cancer

Abstract: Background There is no widely accepted intervention in the prevention of acute mucositis during chemoradiotherapy for head and neck carcinoma. In the present double‐blind study, we tested 4 natural agents, propolis, aloe vera, calendula, and chamomile versus placebo. Methods Patients undergoing concomitant chemo‐intensity‐modulated radiotherapy (IMRT) were given natural agent or matched placebo; grade 3 mucositis on physical examination according to Common Terminology Criteria for Adverse Events (CTCAE) versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(66 reference statements)
0
21
0
4
Order By: Relevance
“…As this study reports about a clinical setting that was not reported previously, this is considered to be initial information that needs confirmation in the future. Propolis was also studied as part of a mixture of 4 natural agents: propolis, Aloe vera, calendula, and chamomile [89]. In this RCT in H&N cancer patients receiving RT, the mixture was reported to be superior to placebo in preventing OM.…”
Section: Discussionmentioning
confidence: 99%
“…As this study reports about a clinical setting that was not reported previously, this is considered to be initial information that needs confirmation in the future. Propolis was also studied as part of a mixture of 4 natural agents: propolis, Aloe vera, calendula, and chamomile [89]. In this RCT in H&N cancer patients receiving RT, the mixture was reported to be superior to placebo in preventing OM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems important that the relevant substances and production methods of bee products in clinical trials are clearly specified. Furthermore, it is important to note that some trials used diluted bee products or combinations of bee products with other substances which might result in negative results [62]. Adverse interactions are possible.…”
Section: Discussionmentioning
confidence: 99%
“…In our reviewed studies, propolis and Aloe vera were reported to alleviate radiation-induced mucositis in Wistar rat model and phase II trial respectively [ 108 , 147 ]. However, Marucci et al conducted double-blind randomized phase III study, reporting that some natural products including propolis and Aloe vera had no effect on acute mucositis during chemoradiotherapy for head and neck carcinoma [ 156 ]. Yet, many natural products such as curcumin, ginger, green tea, honey and Hangeshashinto and so forth still show consistent efficacy in both in vivo, in vitro and clinical trial.…”
Section: Limitations Of the Studiesmentioning
confidence: 99%